Analisis Pengaruh Kualitas Pelayanan, Suku Bunga Kredit Dan Jaminan Terhadap Keputusan Pengambilan Kredit.” (Studi Kasus Pada Pedagang Pasar Beringharjo) - Yunita Fitri Wahyuningtyas; R. Agus Choliq (Jurnal Solusi, 2019)
UMKM business have contributed greatly to the economy of the Special Region of Yogyakarta. UMKM in the Special Region of Yogyakarta continues to develop from year to year. UMKM as many as 220,703 in 2015 continued to increase in 2016 to 230,047 and in 2017 to as many as 238,619 UMKM. Of these, the highest distribution was in Bantul Regency, 26%, and the smallest was in Yogyakarta City, 14% of the total UMKM in Yogyakarta Special Region (Disperindagkoptan DIY, 2018). This study uses a questionnaire with 5 Likert scales that are tested with multiple regression analysis tools to determine whether there is a partial and joint influence between service quality, loan interest rates, and collateral for credit decision making for market traders Beringharjo. Other static tests used were multicollinearity and heteroscedasticity to determine the deviations that occurred in the study. The sampling method used is the accideental sampling technique, which is the selection of samples from a population based on the ease and availability of samples during the duration of the sampling. The sample used was 200 respondents from some of the Beringharjo market traders. In this study there are influences between service quality variables, loan interest rates and collateral for credit decision making at Beringharjo market traders which is indicated by the value of R2 = 73.2%. And the variable that has the highest positive effect is the variable credit interest rate of 3.84, while the lowest variable influence on credit decision making at the Beringharjo market trader is the guarantee variable which is equal to 3.28.